(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The key to a nation’s steady growth is the empowerment of women. In terms of this, the self-help group has a significant influence on how women are empowered in rural areas. SHG works to strengthen the socioeconomic conditions of the community’s most vulnerable members, which supports the nation’s overall economic development. This review article provides a thorough overview of the SHG’s achievements in Prayagraj, Uttar Pradesh’s Chaka Block with regard to women’s empowerment. Nearly all of the research reveals that SHG participants and decision-makers in the democratic, economic, and social realms of life acquire equality of status. This article also offers some suggestions for how to implement SHG successfully. Simple statistical tools were used in this investigation. Based on an analysis of women’s empowerment over self-help groups, the primary results of this study are that self-help groups have a constructive impact on women’s empowerment in the Chaka Block.